The Perception of Organic Foods: Is it Correct? - Vinall, Phil (MD Conference Express, 2014)
The consumer often perceives organic foods as being safer, more nutritious, and in general, better for the environment. After analyzing the published data, however, researchers have concluded that the evidence is inconsistent.